Hak Gugat Pemerintah dalam Mengembalikan Kerugian dan Pemulihan Lingkungan Melalui Sengketa Lingkungan Hidup - Abdul Mubin; Irwansyah Irwansyah (Nagari Law Review, 2017)
The concept or idea of the Ecocracy (Eco-Crasi) suggests that the environment has its own sovereignty called environmental sovereignty. The concept of the eco- nomic places the environment as the subject of law and has the right to obtain legal protection, including the right to compensation and environmental restoration from pollution and environmental destruction. The environment as the subject of law can not be equated with human beings, because the environment can not speak and act as human beings, therefore the environmental rights to demand environmental compensation due to pollution and / or environmental damage are represented to the state, One legal principle in the PPLH Law is the principle of state responsibility, the consequence of the principle of state responsibility, the government may take legal action to represent the environmental interests provided for in Article 90 paragraph (1) of the PPLH Law. The compensation of the environment and the restoration of the environment shall be carried out by means of civil law enforcement instruments such as by filing a civil lawsuit to the court by the agency responsible for the environment, the lawsuit filed on the basis of Legal Acts (PMH) as enshrined in Article 1365 of the Civil Code and the basis of the lawsuit Strict Liability (Strict Liability) as a model of legal liability that does not need to prove the existence of liability without fault as stipulated in Article 88 UUPPLH.